Unformatted text preview: perties of Logarithm Functions) Let g (x) = logb (x) be a
logarithmic function (b > 0, b = 1) and let u > 0 and w > 0 be real numbers.
• Product Rule: g (uw) = g (u) + g (w). In other words, logb (uw) = logb (u) + logb (w)
• Quotient Rule: g u
w = g (u) − g (w). In other words, logb u
w = logb (u) − logb (w) • Power Rule: g (uw ) = wg (u). In other words, logb (uw ) = w logb (u)
There are a couple of diﬀerent ways to understand why Theorem 6.6 is true. Consider the product
rule: logb (uw) = logb (u) + logb (w). Let a = logb (uw), c = logb (u), and d = logb (w). Then, by
deﬁnition, ba = uw, bc = u and bd = w. Hence, ba = uw = bc bd = bc+d , so that ba = bc+d . By
the one-to-one property of bx , we have a = c + d. In other words, logb (uw) = logb (u) + logb (w).
The remaining properties are proved similarly. From a purely functional approach, we can see
the properties in Theorem 6.6 as an example of how inverse functions interchange the roles of
inputs in outputs. For instance, the Product R...
View Full Document